2021
DOI: 10.1016/j.nedt.2021.104796
|View full text |Cite
|
Sign up to set email alerts
|

A survey of E-learning methods in nursing and medical education during COVID-19 pandemic in India

Abstract: Background COVID-19 pandemic has necessitated mandatory e-learning in medical and nursing education. How far are developing countries like India (with wide socioeconomic and cultural diversity) geared up for this challenge remains unexplored. At this critical juncture, we aim to evaluate if online teaching methods are as feasible, acceptable, and effective as in-class teaching for medical/nursing students. Objectives The questionnaire captured: (1) practicability/feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 22 publications
9
119
0
16
Order By: Relevance
“…A study conducted in India had reported that spending a long time in e-learning increases health issues such as headache, eye strain, fatigue, neck pain, back pain, sleep disturbance, loss of concentration, and anxiety among the students. 14,17 The result of the present study indicates that the proportion of the respondents having a positive attitude towards online classes was found comparatively higher than the respondents having a negative attitude. In contrast to the present finding, other studies had reported that most of the students had a negative attitude toward online learning.…”
Section: Positive Attitude Towards Online Classesmentioning
confidence: 53%
See 1 more Smart Citation
“…A study conducted in India had reported that spending a long time in e-learning increases health issues such as headache, eye strain, fatigue, neck pain, back pain, sleep disturbance, loss of concentration, and anxiety among the students. 14,17 The result of the present study indicates that the proportion of the respondents having a positive attitude towards online classes was found comparatively higher than the respondents having a negative attitude. In contrast to the present finding, other studies had reported that most of the students had a negative attitude toward online learning.…”
Section: Positive Attitude Towards Online Classesmentioning
confidence: 53%
“…[5][6][7][8]9,12 In contrast to the present finding studies conducted in India. 6,14 The proportion of the respondent's study in higher classes such as graduation and 51% 49%…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach's alpha was α = .89. The questionnaire includes eight positively worded items [4,5,6,7,8,9,10,13] and six negatively worded items (items 1,2,3,11,12,14). Higher scores indicate higher levels of perceived stress.…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Beginning with the rst lockdown, academic studies in Israel were required to shift to online learning. The transition from on-campus studies to online studies facing screens has signi cantly changed students' habits and lifestyle [3,8,9]. The pandemic and the resultant lockdowns restricting people to their homes can affect both their physical and their mental well-being.…”
Section: Introductionmentioning
confidence: 99%
“…(4). E-learning has been mandated by the University Grants Commission (UGC) for all medical and paramedical students across the country (5). So, consequently, medical schools have moved their focus to e-learning, also called web-based learning, or internet-based learning, to stay non-submerged during the pandemic (6).…”
Section: Introductionmentioning
confidence: 99%